Perbaikan Sistem “Variable Guide Vane” Gas Turbine SGT-100-S ( Studi kasus di PT.ZZZ ) - Zakaria, Tatan; Lesmana, Sandi (Journal Industrial Servicess, 2016)
PT.ZZZ is a private company electric generation who supply an electrical energy demand to one of paper factory in Tangerang, Banten. The electrical energy generated from gas turbine unit fitted with a synchronous generator. The reliability of electricity supply to the customers is preferred PT.ZZZ, so they have a target of "Zerro Unplan Shutdown". However, based on historical data found that the Gas Turbine frequent stop by unplanned maintenance (unplan shutdown) caused mostly by a system of control "Variable Guide Vane (VGV)". Through analysis of RCA (Root Cause Analysis)  found a variety of different causes of system failure VGV, so one by one it have been repaired. Before improvement was found VGV failure data as much  fourteen times, and after improvement become zero times.